Games in code form-introducing a new games representation - Ferreira, M. A. M.; Matos, M.; Filipe, J. A. (International Journal of Academic Research, 2014)
The objective of this paper is to present a new representation for games with more than two players. This formalization concentrates the consequences of the various strategies without the suppression of the extensive form details. In other words, this representation supplies simultaneously the whole information that the extensive and normal forms establish separately. Some games are presented in order to illustrate these ideas. Keywords: Games theory, extensive form, normal form, code form